Dairy marketing by intra-urban, peri-urban and rural dairy producers near Addis Ababa, Ethiopia - Debrah, S.K. (International Livestock Centre for Africa, 1992)
This paper reports on a study conducted on the marketing options and patterns of three categories of dairy producer: intra-urban producers, peri-urban producers and rural producers within an 85km radius of Addis Ababa, Ethiopia. The range of marketing outlets available to each category of producer was identified, and the relative intensities of outlet use and the factors influencing producer choice of alternative market outlet for the different producer groups were analysed. The sample, consisting of 173 dairy producers representative of the three categories of producer, was interviewed on seven consecutive days in March, May and June 1986. Sixty-nine per cent of the total volume of intra-urban producer sales and 96 percent of that of peri-urban producers was sold to institutions in Addis Ababa despite the higher net prices offered by direct sales to individual consumers. Large producers consider the high labour costs of selling milk directly to individual consumers too high relative to the costs of delivering milk in bulk to the institutions. Rural producers located near fresh milk collection centres sold almost all their milk at the collection centres. Their proximity reduces the costs of transportation, thereby making the net prices relatively higher than the price they would obtain by transporting their milk for sale in Addis Ababa.